Interleukin-6 in Spontaneous and Induced Vaginal Birth and Neonatal Outcomes: A Cross-Sectional Study - Torkzahrani, Shahnaz; Sahebazzamani, Zahra; Shahsavari, Soodeh; Behroozi Lak, Tahereh (Advances in Nursing & Midwifery, 2020)
Introduction: The detailed mechanisms fundamentally the onset of spontaneous labor at term remain obscure. Delayed labor means slower progress of the birth process and is associated with childbirth problems and negative birth feelings, resulting in subsequent pregnancy and labor. Inflammatory mechanisms are thought to play a vital role in the physiology of parturition and labor in pre-term and spontaneous term birth. Studies indicated that the mode of birth and labor change interleukin-6 concentrations in maternal and fetal sections. The immunobiological role of inflammatory cytokines in parturition and the onset of spontaneous labor at term, especially without exogenic motivation, remain unspecified yet. The specific role of Interleukin - 6 (IL - 6) in the biosynthesis of prostaglandins, myometrium contractions, cervix ripening, and finally, its role in the process of labor is reported in studies. According to the changes in the physiology of normal birth in induced labor, this study aimed to compare the mean level of IL-6 in pregnancies terminated by selective induction or spontaneous vaginal birth and neonatal outcome. Methods: This cross-sectional study was conducted on two groups of 40 women with spontaneous and induced birth. All pregnancies were term without clinical or obstetric complications. The enzyme-connected immunosorbent assay measured the level of IL - 6 in the umbilical cord. The obtained data were analyzed by SPSS 22 software. Results: The mean level of IL-6 in the umbilical cord was not significantly different in spontaneous (250.20 ± 39.36 pg./ml) and induced labor (240.97 ± 39.06 pg./ml) (P = 0.847). In the spontaneous birth group, the first and fifth minute Apgar scores were higher than the induced labor group (P = 0.021). None of the infants required resuscitation or NICU hospitalization in the neonatal unit. Approximately 97.5% of infants were breastfed in the induced birth group. Only one of the newborns in the induced birth group had jaundice and underwent phototherapy for 8 hours at home. In this study, there was found no association between IL - 6 and pregnancy/infant variables. Conclusions: Our results indicate that the birth method (induced and spontaneous) had no effect on the level of IL-6 in the umbilical cord blood, but the birth method had just a significant effect on the Apgar score. Induction of labor is associated with adverse birth outcomes. This study investigated interleukin-6 in cord blood in term newborns depending on the mode of delivery and labor. Delayed labor means slower progress of the birth process and is associated with childbirth problems and negative birth feelings, which can have consequences on subsequent pregnancy and labor. We determined whether normal spontaneous birth and induced birth at term was associated with poor newborns outcomes. Current study was a different view helping future studies to investigate other aspects of post term pregnancy and supporting physiological parturition